Two new species of the genus Pseudotritoma Gorham, 1888 (Coleoptera: Erotylidae) from China - Liu, Jing; Zhang, Bing-Qian; Li, Jing (Zootaxa, 2024)
Two new species of the genus Pseudotritoma Gorham, P. bicolorata Liu & Li, sp. nov. and P. rufobrunnea Liu & Li, sp. nov., are described and illustrated. A key to all known species of Pseudotritoma from China is presented.